The Contribution of the Environmental Management System to the achievement of Occupational health and Safety for employees of Algerian Industrial Enterprises: an empirical study of cement company Ain touta Batna - Ali, Ammarisamir; Djamel Eddine, Ikhlef (International Journal of Psychosocial Rehabilitation, 2022)
This study aimed to clarify how the Environmental Management System contributes to the achievement of occupational health and safety for employees of Algerian industrial enterprises, through a case study of one of the Algerian industrial companies, represented by Ain Touta Cement Company in Batna. This study concluded that the adoption of this system contributes to the achievement of occupational health and safety for the employees of the enterprises under study, through the positive impact that this system has on their physical and psychological health through the fight against pollution, which is a source of organic diseases. That infects them.